MLL-AF4 upregulates 5-lipoxygenase expression in t(4;11) leukemia cells via the ALOX5 core promoter - Hyprath, Marius; Molitor, Maximilian; Schweighöfer, Ilona; Marschalek, Rolf; Steinhilber, Dieter (Frontiers in Pharmacology, 2025)
5-Lipoxygenase (5-LO), encoded by the gene ALOX5, is implicated in several pathologies. As key enzyme in leukotriene biosynthesis, 5-LO plays a central role in inflammatory diseases, but the 5-LO pathway has also been linked to development of certain hematological and solid tumor malignancies. Of note, previous studies have shown that the leukemogenic fusion protein MLL-AF4 strongly increases ALOX5 gene promoter activity. Here, we investigate the upregulation of ALOX5 gene expression by MLL-AF4. Using reporter assays, we first identified the tandem GC box within the ALOX5 promotor sequence as the main target of MLL-AF4. Subsequently, we narrowed down the domains within the MLL-AF4 protein responsible for ALOX5 promoter activation. Our findings indicate that MLL-AF4 binds to the ALOX5 promoter via its CXXC domain and that the AF9ID, pSER and CHD domains redundantly activate transcriptional elongation. Knockdown of the MLL-AF4 gene in the human B cell line SEM revealed that MLL-AF4 is an inducer of ALOX5 gene expression in leukemic cells with lymphoid properties. Finally, we found that the MLL-AF4-related protein MLL-AF9, a driver of acute myeloid leukemia, similarly acts on the ALOX5 promoter. Taken together, we show that two prominent MLL fusion proteins are ALOX5 gene inducers in cells with lymphoid features.